Da'wah, Internet, and Social Reality - Mukhtidinov, Rashid; Firdausi, Putri Nadiyatul (Institut Agama Islam Syarifuddin Lumajang, 2024)
This article discusses the relationship among da'wah, internet-based social media, and social reality. A number of theories are used to build a relational perspective between these three things, including the social construction theory of Peter L. Berger and Thomas Luckmann. This study using a literature study approach resulted in the conclusion that Islamic preaching media always have the opportunity to shape people's thinking patterns. However, each content creator is always faced with other Islamic narratives originating from other channels. Discourse contestation regarding Islamic teachings cannot be avoided in the current era of open information. Social media is a channel for disseminating information regarding this matter, which is a reflection that the Cyber-Islamic Environment has been well developed in this country. Apart from being a learning medium, social media has also become a space for movement. Activism finds wide space on social media channels, and is able to penetrate the space and time of its users. Da'wah and activities to spread the wings of the community are increasingly open.